The Relationship Between Birth Weight and a Number of Body Measurements of Neonates at Dr. Pirngadi Hospital Medan - Nurhayati Hamid; Helmi Lubis; Martinus Saragih; Rafita Ramayati; Chairuddin P. Lubis; Dachrul Aldy; Noersida Raid (Indonesian Pediatric Society, 1983)
From January 1980 to November 1980 a survey on the relationship between birth weight (BW) with body length (BL), head circumference (HC) and chest circumference (CC) was carried out on 1689 newborn infants bom in the Dr. Pringadi General Hospital Medan. They were divided into six groups, based on their BW i.e.: Group I : 1501 - 2000 g Group II : 2001 - 2500 g Group Ill : 2501 - 3000 g Group IV : 3001 - 3500 g Group V : 3501 - 4000 g G1011p VI : 4001 - 4500 g The average of BL, HC and CC in cm is shown below: The mean values of total BL, total HC and total CC can represent the anthropometric values for the certain BW group. No significant differences were found between male and female newborn infants in each group.